Puppy puzzle Who can tell these puppies apart? - Daniels, Lucy; Howard, Paul (London, Hodder Children's Books, 1996)
It's pet day at school, and Mandy has to help out when a puppy goes missing! This title is part of the "Animal Ark" series that provides animal stories for younger readers.
Keywords: English fiction